2003
DOI: 10.2172/918344
|View full text |Cite
|
Sign up to set email alerts
|

Algorithmic support for commodity-based parallel computing systems.

Abstract: Follows 3 AbstractThe Computational Plant or Cplant is a commodity-based distributedmemory supercomputer under development at Sandia National Laboratories. Distributed-memory supercomputers run many parallel programs simultaneously. Users submit their programs to a job queue. When a job is scheduled to run, it is assigned to a set of available processors. Job runtime depends not only on the number of processors but also on the particular set of processors assigned to it. Jobs should be allocated to localized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 89 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…Our work also led to a linear-time dynamic programming algorithm for the 1-dimensional problem of points on a line or ring; see Leung et al [17] for details.…”
Section: Our Resultsmentioning
confidence: 98%
“…Our work also led to a linear-time dynamic programming algorithm for the 1-dimensional problem of points on a line or ring; see Leung et al [17] for details.…”
Section: Our Resultsmentioning
confidence: 98%
“…[25]. However, we are not aware of other strategies than UDFlex [26] that utilize a topology agnostic routing algorithm to achieve routing-containment for irregular partitions.…”
Section: Related Workmentioning
confidence: 99%
“…Since job placement affects the system's network contention, allocation is a major factor in determining system performance, particularly in commodity-based supercomputers such as Cplant, which typically have higher communication latencies and lower bandwidth than supercomputers with custom networks. Experiments on Cplant showed that poor allocation could increase the running time of a pair of highcommunication jobs by as much as a factor of two [17]. Other researchers have shown in a variety of studies that interprocessor communication can reduce throughput [2,20,21,24].…”
Section: Introductionmentioning
confidence: 99%